2006
DOI: 10.5194/acp-6-4117-2006
|View full text |Cite
|
Sign up to set email alerts
|

Observations of lunar tides in the mesosphere and lower thermosphere at Arctic and middle latitudes

Abstract: Abstract. Meteor radars have been used to measure the horizontal winds in the mesosphere and lower thermosphere over Castle Eaton (52 • N) in the UK and over Esrange (68 • N) in Arctic Sweden. We consider a 16-year data set covering the interval 1988-2004 for the UK and a 6-year data set covering the interval 1999-2005 for the Arctic. The signature of the 12.42-h (M 2 ) lunar tide has been identified at both locations. The lunar tide is observed to reach amplitudes as large as 11 ms −1 . The Arctic radar has a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 27 publications
2
45
2
Order By: Relevance
“…These atmospheric tides are considerably smaller in amplitude than the dominant, atmospheric thermal tide of the Sun (Chapman & Lindzen 1970;Vial & Forbes 1994;Sandford et al 2006). The dominant component of the lunar atmospheric tide is the M 2 tide with a period of 12.42 h (Chapman & Lindzen 1970;Sandford et al 2006;Forbes et al 2013).…”
Section: Lunar Tidesmentioning
confidence: 99%
See 2 more Smart Citations
“…These atmospheric tides are considerably smaller in amplitude than the dominant, atmospheric thermal tide of the Sun (Chapman & Lindzen 1970;Vial & Forbes 1994;Sandford et al 2006). The dominant component of the lunar atmospheric tide is the M 2 tide with a period of 12.42 h (Chapman & Lindzen 1970;Sandford et al 2006;Forbes et al 2013).…”
Section: Lunar Tidesmentioning
confidence: 99%
“…These atmospheric tides are considerably smaller in amplitude than the dominant, atmospheric thermal tide of the Sun (Chapman & Lindzen 1970;Vial & Forbes 1994;Sandford et al 2006). The dominant component of the lunar atmospheric tide is the M 2 tide with a period of 12.42 h (Chapman & Lindzen 1970;Sandford et al 2006;Forbes et al 2013). According to Chapman & Lindzen (1970), there are as many as 30 components comprising the lunar tide, most of which are much smaller in amplitude and, therefore, are often ignored due to the limited ability of measurements to detect their small signal (Sandford et al 2006).…”
Section: Lunar Tidesmentioning
confidence: 99%
See 1 more Smart Citation
“…• N, 21.1 • E), Sandford et al (2006) found the lunar tide has maximum amplitudes in winter (January-February) with a second autumnal (September-October) maximum. At Wuhan there is a second northward amplitude peak in July and an eastward peak in August.…”
Section: Lunar Tidementioning
confidence: 99%
“…Lunar age is a measure of the phase of the Moon, where ν=0 signifies new moon (Stening et al, 1997(Stening et al, , 2003. This method has been used to successfully by Sandford et al (2006) and Stening et al (1997Stening et al ( , 2003. Because high spectral resolution is required to separate the Lunar M 2 and Published by Copernicus GmbH on behalf of the European Geosciences Union.…”
Section: Data and Analysismentioning
confidence: 99%